Reduction in circulating Endothelin-1 levels by inhaled COPD medications - Sato, Hiroki; Nagano, Tatsuya; Suraya, Ratoe; Hazama, Daisuke; Umezawa, Kanoko; Katsurada, Naoko; Yamamoto, Masatsugu; Tachihara, Motoko; Nishimura, Yoshihiro; Emoto, Noriaki; Kobayashi, Kazuyuki (Respiratory medicine, 2025)
Chronic obstructive pulmonary disease (COPD) can be complicated by pulmonary hypertension (PH), impacting prognosis and quality of life. Endothelin-1 (ET-1) is implicated in PH development and elevated in COPD patients. The impact of COPD treatments on ET-1 and COPD-related PH remains unclear. This study investigated changes in ET-1 levels after administration of inhaled COPD medications and explored underlying mechanisms. Patients underwent pulmonary function tests, COPD Assessment Test, and plasma ET-1 measurement before and 4–12 weeks after treatment initiation. In mice, elastase-induced emphysema was treated with budesonide (BUD), glycopyrronium (GLY), and formoterol (FOR) combinations for 2 weeks. Plasma ET-1 concentration and cytokine expression were analysed. HULEC-5a cells were used to examine ET-1 expression after TNFα stimulation. The study included 33 patients. COPD patients (n = 24) showed higher baseline plasma ET-1 levels compared to controls (n = 9) (2.12 pg/ml vs 1.54 pg/ml, p < 0.001). Plasma ET-1 levels decreased in COPD patients posttreatment (2.12–1.82 pg/ml, p = 0.004), with reductions observed across all disease stages and treatment regimens. Mice showed elevated ET-1 levels and expression of inflammatory cytokines after elastase instillation. BUD/GLY/FOR treatment significantly reduced ET-1 concentration and TNFα expression. Furthermore, TNFα stimulation upregulated ET-1 expression in HULEC-5a cells. In COPD patients conventional treatment decreased ET-1 concentration. In mouse models TNFα expression was suppressed by BUD/GLY/FOR. In HULEC-5a cells, TNFα stimulation exerted an increased ET-1expression. These findings suggest that the suppressive effect of inhaler therapy on ET-1 expression is due to the anti-inflammatory effects of these drugs. •Patients with COPD have an elevated plasma level of ET-1.•Inhaler therapy induces a decrease in plasma ET-1 levels in COPD patients.•ET-1 levels and TNFa expression are elevated in COPD mouse models.•Treatment for COPD mouse models exhibited a decrease in ET-1 levels and TNFα expression.•TNFα stimulation induced expression of ET-1 in endothelial cells.